2019
DOI: 10.1108/lm-02-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

Library stakeholder attitudes and new technology

Abstract: Purpose The purpose of this paper is to provide advice for library managers on the collection of feedback from stakeholders. An example of radio frequency identification (RFID) is used to illustrate what can be learned and how decisions can be improved with this feedback. Design/methodology/approach The stakeholder, RFID and library literature are reviewed and lessons for improving future technology decisions are developed. The results of a direct-mail survey of 394 members of the general public in the Midwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Librarians are often considered to be early adopters of new service technologies (Larson, 2018). Fraser-Arnott (2022) analysed the mission statements of 80 public libraries and found that the mission of public libraries can be summarised in seven areas: community building, cultural and recreation, educational and learning, equitable access, positive impact, information, and stewardship.…”
Section: The Technological Advancements In Librarymentioning
confidence: 99%
See 1 more Smart Citation
“…Librarians are often considered to be early adopters of new service technologies (Larson, 2018). Fraser-Arnott (2022) analysed the mission statements of 80 public libraries and found that the mission of public libraries can be summarised in seven areas: community building, cultural and recreation, educational and learning, equitable access, positive impact, information, and stewardship.…”
Section: The Technological Advancements In Librarymentioning
confidence: 99%
“…Iglesias (2013) pointed out the inevitability of library automation. A number of recent studies suggest that most library stakeholders welcome technological innovations in libraries (Harisanty et al, 2022;Lembinen, 2021;Larson, 2018).…”
Section: The Technological Advancements In Librarymentioning
confidence: 99%
“…Information collection and other privacy concerns may influence various attitudes and behaviors. Privacy concerns have been linked with interest in buying non-genetically-modified produce and cereal, interest in buying antibiotic-free and humanely-raised meat, support for adding radio frequency identification chips to car license plates, use of shopping lists, and even reactions to product stockouts in stores (Larson, 2018(Larson, , 2019b(Larson, , 2020a(Larson, , 2022Larson and Ferrin 2023). These relationships suggest that privacy concern measures may help explain many consumer choices.…”
mentioning
confidence: 99%